Developed Informality in Developing Countries. The Book Review On: Linking the Formal and Informal Economy: Concepts and Policies / Ed. by B. Guha-Khasnobis, R. Kanbur, E. Ostrom. Oxford: Oxford University Press, 2006. - БарсуковаСветлана Юрьевна (Journal of Economic Sociology, 2010)
Detailed description in the text